Delayed Encephalopathy of Carbon Monoxide Intoxication and Treatment with Hyperbaric Oxygen: A Case Report - Fatma Polat; Nur Yüceyar; Ali Akay; Ayşe Sağduyu Kocaman (Türk Nöroloji Dergisi, 2012)
Delayed encephalopathy (DE) is a neuropsychiatric syndrome that can arise generally within 20 days of acute carbon monoxide (CO) intoxication after apparent recovery and involves variable degrees of cognitive deficits, personality changes, movement disorders and focal neurologic deficits. We report a 35-year-old female patient with delayed encephalopathy due to CO intoxication, presenting with cognitive impairment and mild parkinsonism despite receiving hyberbaric oxigen therapy (HBO). Magnetic resonance imaging showed abnormal signal intensity and decreased diffusivity at both caudate nuclei and globus pallidus. She continued to receive additional HBO therapy and complete recovery was reached within six months. The positive effect of early HBO therapy of selected patients in reversing the acute effects of CO intoxication is appearant. We here also review the beneficial effect of HBO in preventing or limitating the late neurocognitive deficits associated with severe CO intoxication